Oriostoma (Gastropoda) with an in situ operculum from the Silurian of Indiana. (May 2021) - Rohr, David M.; Wahlman, Gregory P.
Abstract: A single specimen of Oriostoma globosum (von Schlotheim, 1820 ) from the Silurian-age (Wenlockian) Laurel Limestone in southeastern Indiana preserves a partial, multispiral operculum in situ within the aperture. Only eight specimens of in situ Oriostoma opercula have previously been illustrated from Canada and Europe, and this is the first from the United States. Oriostoma huntingtonensis Kindle, 1904, from younger Silurian (Ludlovian–Pridolian) strata in northern Indiana is considered a synonym of the more widespread O. globosum, and it was described as having associated loose multispiral calcareous opercula in the same strata.